2016
DOI: 10.1084/jem.20151100
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary restriction improves repopulation but impairs lymphoid differentiation capacity of hematopoietic stem cells in early aging

Abstract: Dietary restriction (DR) improves health, delays tissue aging, and elongates survival in flies and worms. However, studies on laboratory mice and nonhuman primates revealed ambiguous effects of DR on lifespan despite improvements in health parameters. In this study, we analyzed consequences of adult-onset DR (24 h to 1 yr) on hematopoietic stem cell (HSC) function. DR ameliorated HSC aging phenotypes, such as the increase in number of HSCs and the skewing toward myeloid-biased HSCs during aging. Furthermore, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 102 publications
(128 reference statements)
7
100
3
4
Order By: Relevance
“…Although the effects of CR on physiology have been found to promote health, a recent study by Tang et al [24•] suggests that caloric restriction may exert both beneficial and adverse effects on hematopoiesis. It has been observed that during aging in C57BL/6 mice, HSCs expand in number but have reduced functionality, such as lowered self-renewal capability and skewing of differentiation towards the myeloid lineage, due to stress associated with active HSC cycling [25].…”
Section: Caloric Restrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effects of CR on physiology have been found to promote health, a recent study by Tang et al [24•] suggests that caloric restriction may exert both beneficial and adverse effects on hematopoiesis. It has been observed that during aging in C57BL/6 mice, HSCs expand in number but have reduced functionality, such as lowered self-renewal capability and skewing of differentiation towards the myeloid lineage, due to stress associated with active HSC cycling [25].…”
Section: Caloric Restrictionmentioning
confidence: 99%
“…It has been observed that during aging in C57BL/6 mice, HSCs expand in number but have reduced functionality, such as lowered self-renewal capability and skewing of differentiation towards the myeloid lineage, due to stress associated with active HSC cycling [25]. Four to nine months of caloric restriction in mice increases HSC quiescence and prevents age-related increases in HSC numbers, suggesting that CR conditions are beneficial in reducing proliferation-associated stress [24•]. CR conditions also rescue HSC skewing towards the myeloid lineage, as the number of lymphoid-biased HSCs and myeloid-biased HSCs are similar.…”
Section: Caloric Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of hematopoietic stem cells in BM was changed with aging and the function of repopulation as stem cells in vivo diminished when hematopoietic stem cells form aged mice were transplanted along with competitor cells. Diet restriction restored not only the number of stem cells but also the repopulation capacity [31, 32]. In this study, the number of colonies was not different between SF and NC mice in the first, secondary, and tertiary courses.…”
Section: Discussionmentioning
confidence: 61%
“…Although global changes to the epigenome occur during aging, it is more likely that the functional decline in aging HSCs is due to specific changes to key regulatory loci. Examining the molecular changes associated with other approaches of rejuvenating old HSCs such as transcription factor-based reprogramming to induced HSCs (iHSCs) 70,71 , calorie restriction 72 , or exposure to a young circulatory system through parabiosis 73 may identify epigenetic differences at critical loci which enforce the aging phenotype. Reversal of these specific modifications may provide a mechanism to restore self-renewal and lymphoid differentiation potential to old HSCs.…”
Section: Is Aging a Byproduct Of Hsc Epigenome Changes Over Time?mentioning
confidence: 99%